PROFESSIONAL ACTIVITY AND DEVELOPMENT STAGES OF ENGINEERS IN THE WORLD EDUCATION SYSTEM (Academicia Globe: Inderscience Research, 2022)
This article is devoted to the identification and improvement of the professional activities and stages of development of engineers in the global education system.